Tradition and Revolution in the Formation of the State in Post-Independent Chile: The Provincial Assemblies (1822-1830) [Tradición y Revolución en la Formación del Estado en Chile Post-Independiente: Las Asambleas Provinciales (1822-1830)] - Garcia - Huidobro-Becerra, C (Universitat Pompeu Fabra, 2018)
The object of this paper is to study the emergence and development of provincial assemblies in Chile during the post-independence period, encompassing from 1822 to 1830. Another objective of this research consists of studying the impact that these assemblies had on the conformation of the Chilean State, especially if it is considered that these institutions became a larger expression of the municipal government inherited from the Ancien Régime, somehow keeping alive the legal principles and political doctrines of this system in an uneasy coexistence with the ideas of the revolution in Spanish America. © 2018 Universitat Pompeu Fabra. All rights reserved.